Pancasila Sebagai Dasar Negara Kesatuan Republik Indonesia Perspektif Al-Qur’an : Analisis Hermeneutika Hans Georg Gadamer - Sunardi, Sunardi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This article describes the values ​​of Pancasila from the perspective of the Qur'an and this paper uses Gadamer's "fusion of horizon" theory as a tool for analysis. Indonesia is a multicultural country and a variety of religions, ethnicities, languages ​​and distinctive values ​​that show Indonesian values. Therefore, to form a country into a unified state, Pancasila is the unifier and religion is the belief and ideology of each individual. Looking at the text of the Al-Qur'an from the first precepts shows that from the divine side, it is very Qur'anic because it practices the values ​​of the Qur'an. The second precept of the Al-Qur'an calls for justice and human values ​​as the concept of a state and religion. The third precept expressly states that the Al-Qur'an strongly recommends the values ​​of unity as a whole. The four precepts developed by the Indonesian state are based on the concept of the Qur'an which strongly advocates democracy (musyawarah). The five precepts of the Indonesian state are built on the values ​​of welfare and social justice, which are the principles of the Al-Qur'an and the Al-Qur'an which threatens social discrimination